2010
DOI: 10.1002/ceat.200900496
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior and Structure of a Commercial Esterquat Surfactant Aqueous System

Abstract: Aqueous dispersions of a commercial esterquat-type surfactant widely used in fabric softeners were rheologically characterized. While at 4 wt % esterquat concentration, a Newtonian response was observed; non-Newtonian (Sisko) flow behavior and viscoelastic properties were found at 12 wt % and higher concentrations. The onset of nonlinear viscoelasticity in oscillatory shear provided interesting information on the strength of quiescent surfactant aggregates. Mechanical spectra corresponded to the plateau zone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…However, a typical formulation of liquid softener may also contain nonionic surfactant, antibacterial and preservative agents, dyes, and fragrances [19]. New data and information provided by this work completes previous studies of systems with T1 surfactant [16,20] and contributes relevant information for scientific research and industrial application.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…However, a typical formulation of liquid softener may also contain nonionic surfactant, antibacterial and preservative agents, dyes, and fragrances [19]. New data and information provided by this work completes previous studies of systems with T1 surfactant [16,20] and contributes relevant information for scientific research and industrial application.…”
Section: Introductionsupporting
confidence: 63%
“…Upon increasing shear rate, the shear stress increased after a certain shear time period indicating the possible appearance of antithixotropy, if the build-ups of viscosity were reversible after a certain rest time. However, previously reported results on these systems revealed that the viscosity build-up phenomena turned out to be irreversible at least for a very long period of rest time [16]. Therefore, this behavior will be called apparent antithixotropy.…”
Section: Start-up At the Inception Of Shear Experimentsmentioning
confidence: 93%
See 2 more Smart Citations
“…This corresponded to the plateau zone of the mechanical spectrum. This window of the mechanical spectrum is related in polymer rheology to the occurrence of macromolecular entanglements [15] and has also been found in concentrated emulsions [16], concentrated solutions of polymers [17,18], micellar solutions [19], and in a protein-polysaccharide system in aqueous dispersions [20]. A similar behavior to that of this suspoemulsion has been found for hydrophobically modified alkali-soluble emulsions [21].…”
Section: Rheological Characterizationmentioning
confidence: 65%